BENEFITS OF REGULATORY AND VOLUNTARY SUSTAINABILITY STANDARDS COMPLIANCE: A REVIEW ON MALAYSIAN PALM OIL - Abdullah, I.; Wan Mahmood, W.H.; Md Fauadi, M.H.F.; Ab Rahman, M.N. (Journal of Advanced Manufacturing Technology (JAMT), 2015)
Compliance to regulatory and voluntary standard is one of the most important elements of sustainability in palm oil production. This paper assessed key regulatory and voluntary standards as references in relation to sustainability in Malaysian palm oil. It also analysed benefits of regulatory and voluntary standards compliance based on literature reviews. The findings showed that the compliance to regulatory and voluntary standards for the Malaysian palm oil production could improve main elements of sustainability like environmental, social, and economic performance. Besides, the goal of economic performance could also be achieved by increasing social and environmental performance.